Adiposity Measurements and Metabolic Syndrome Are Linked Through Circulating Neuregulin 4 and Adipsin Levels in Obese Adults - Guo, Dan; Liu, Jianfang; Zhang, Peizhen; Yang, Xiaoyu; Liu, Deying; Lin, Jiayang; Wei, Xueyun; Xu, Bingyan; Huang, Chensihan; Zhou, Xuan; Teng, Fei; Zhu, Hong; et al. (Frontiers in Physiology, 2021)
Background: Adiposity and adipokines are associated with metabolic disorders, but little is known regarding that whether adiposity measurements link metabolic syndrome (MetS) through circulating neuregulin 4 (Nrg4) and adipsin levels. Methods: A total of 1212 subjects with a waist circumference greater than 90 cm for men or 80 cm for women were enrolled from a Chinese community. Circulating Nrg4 and adipsin levels were measured using commercial kits. Mediation analyses of circulating Nrg4 and adipsin were performed in the study using linear and logistic regression. Results: Subjects with MetS had higher waist circumference, visceral fat level, and circulating adipsin level, and lower levels of circulating Nrg4 and muscle mass to visceral fat (MVF) ratio (all P < 0.05). In multivariable logistic regression analyses, after adjusting for confounding variables, per standard deviation (SD) increase in waist circumference and visceral fat level were significantly associated with increased odds of MetS [OR (95% CI), 1.42(1.22-1.64); 2.20(1.62-2.99); respectively]; and per SD reduction in MVF ratio was significantly associated with reduced odds of MetS [OR (95% CI), 0.65(0.55-0.77)]. In the mediation analyses, both circulating Nrg4 and adipsin levels mediated the association between waist circumference (8.31% and 18.35%, respectively), visceral fat level (7.50% and 9.98%, respectively), and MVF ratio (5.80% and 9.86%, respectively) and MetS after adjustments. Conclusions: These findings indicate that adiposity measurements and MetS are linked through circulating Nrg4 and adipsin levels in obese adults, suggesting that circulating Nrg4 and adipsin levels might be potential predictors for management of MetS.